Robot‑assisted resection of a rare bladder tumor facilitated by perioperative bladder wall tattooing - Michal Balík; Pavel Navrátil; Lucie Šmejkalová; Miloš Broďák (Videosurgery and Other Miniinvasive Techniques)
Inflammatory myofibroblastic tumors (IMTs) of the bladder are rare, with a limited number of cases reported in the literature. Complete resection with negative margins is essential to reduce the risk of recurrence, while bladder function preservation is also crucial for the patient. This study describes a 56‑year‑old patient with a bladder dome IMT managed using robot‑assisted partial cystectomy facili tated by perioperative cystoscopic tattooing to precisely demarcate the tumor margins. The procedure began with cystoscopic tattooing of the lesion using Black Eye dye, followed by robotic resection with the da Vinci Xi system. Complete transmural resection and a 2‑layer bladder closure were performed, with preservation of the bladder capacity. The patient experienced minimal blood loss, no intraopera tive complications, and was discharged 2 days after the procedure. Follow‑up examinations, including cystoscopy and computed tomography, confirmed no recurrence 12 months after surgery. Cystoscopic tattooing facilitated clear intraoperative tumor localization, enabling precise resection and minimal bladder wall loss. This approach addressed a key challenge of robotic bladder surgery—lack of tactile feedback—while maintaining functional outcomes. Robot‑assisted partial cystectomy with cystoscopic tattooing represents a promising alternative to maximal transurethral resection, especially in the context of bladder‑sparing trimodal therapy, for patients who are not eligible for or unwilling to undergo radical cystectomy. This technique is particularly relevant given the increasing focus on minimally invasive procedures and advancements in systemic therapy. In the future, this method could be adapted for ureteral robotic surgeries to enhance lesion localization.